Atlas of organ transplantation - Humar, Abhinav. (Springer, 2006)
A comprehensive compilation of the majority of surgical procedures in transplant surgery, this book details the latest and most innovative procedures in one reference work. Atlas of Organ Transplantation is essential reading for all transplant surgeons, residents and fellows, as well as operating room nurses and transplant nurse coordinators. Multiorgan procurement from the deceased donor - Dialysis access procedures - Nephrectomy from a living donor - Kidney transplantation - Pancreas transplantation - Liver transplantation - Intestinal and multivisceral transplantation.